Nuclear charge radii of 8,9Li determined by laser spectroscopy - Ewald, Günter; Kluge, Heinz-Jürgen (Physical review letters, 2004)
The 2s→3s transition of 6,7,8,9Li was studied by high-resolution laser spectroscopy using two-photon Doppler-free excitation and resonance-ionization detection. Hyperfine structure splittings and isotope shifts were determined with precision at the 100 kHz level. Combined with recent theoretical work, the changes in the nuclear-charge radii of 8,9Li were determined. These are now the lightest short-lived isotopes for which the charge radii have been measured. It is found that the charge radii monotonically decrease with increasing neutron number from 6Li to 9Li.
Gesehen am 27.02.2020